Institutionalising Urban Climate Action: Recent Recognitions - Ama Kissiwah Boateng (European Scientific Journal, ESJ, 2023)
With in-depth knowledge of the urban climate governance literature, studies of this nature have yet to be fully explored in the context of institutionalisation. Knowing which aspects are well-researched and where in contrast, research gaps lie, this paper systematically reviews the relevant literature to understand how urban climate governance has been institutionalised in cities and municipalities by following the Preferred Reporting Items for Systematic Reviews (PRISMA) and analysing English language journal articles published between 1990 and 2020 in the Web of Science database. As the concept of institutions is becoming more prominent in urban climate change literature, the findings indicate that urban adaptation was mentioned more frequently than mitigation, among other topics. Moreover, the research gaps encompass several institutional challenges associated with urban climate governance. Therefore, one essential step is to focus on new institutional arrangements for advancing climate goals across multiple localities.